Human sex development: targeted technologies to improve diagnosis. Issue 1 (December 2016) - Buonocore, Federica; Achermann, John
Abstract A new study of disorders of sex development presents an improved targeted next-generation sequencing approach for their diagnosis. Please see related Research article:http://genomebiology.biomedcentral.com/articles/10.1186/s13059-016-1105-y .